فهم معنى "بلدة طيبة و رب غفور" لبناء مجتمع إسلامي في المجتمعات مختلفة الأديان - Yulius bin Abdul Muis (Al-Zahra: Journal for Islamic and Arabic Studies)
This paper aims to reveal the broader and deeper meaning of the sentence: baldatun thayyibatun wa rabbun ghafur. this sentence contained in surah Saba:15, which is very popular in the Islamic community when they refer to a safe, prosperous country and it’s people are blessed by God with forgiveness. Disclosure of the meaning of baldatun thayyibatun wa rabbun ghafur more broadly and deeply is in order to find an operational foundation to build an Islamic society in a society of different religions, both for the present and the future. The method used in this study is the study of literature by trying to understand more deeply, in detail and comprehensive the sentence Baldatun Tahayyibatu wa Rabbun Ghafur through the explanation of various books of tafseer, then the meanings are summed up into several main points. Contextually, the verse 15 of the surah Saba is Allah addressed it to the land of Saba and its people. With the title "baldatun thayyibatun wa rabbun ghafur", which is Allah fond of for the country of Saba and its inhabitants shows that the inhabitants of the country of Saba at that time were believed to always maintain and behave with Islamic values in their daily lives under the mukmin leadership and fair. The main values contained in the sentence of “baldatun thayyibatun wa rabbun ghafur” such as tawhed, gratitude, ukhwah and advising fellow Muslims, and the values are relevant to be used as a reference and basis in building an Islamic society in the midst of different religious communities, in the present and future. Therefore, a strong commitment must be built from each Muslim individual in practicing and upholding what are the main values contained in the sentence of “baldatun thayyibatun wa rabbun ghafur”, so that Islamic society will be realized wherever Muslims areز